Instructional design and educational satisfaction for virtual environment simulation in undergraduate nursing education: the mediating effect of learning immersion - So Young Park; Jung-Hee Kim (BMC Medical Education, 2022)
Abstract Background Schools were closed after the onset of COVID-19, with non-face-to-face practices or distance education in nursing education replacing video learning or simulation classes in nursing education clinical practicum. This led to an increase in interest in virtual environment simulation education. While technology-based teaching methods might feel new and intriguing to learners, it is necessary to evaluate learner satisfaction with such an educational method beyond its novelty value. Therefore, this study examined the mediating effect of learning immersion on the relationships between instructional design and educational satisfaction, for virtual environment simulation. Methods A descriptive cross-sectional research design was used. The study sample included students in the third or fourth year of the nursing curriculum in South Korea. The participants were 164 nursing students, who had an experience with virtual environment simulation practices during the past year, prior to September 2021. Data were collected using an online questionnaire. The questionnaire addressed the characteristics of nursing students, instructional design, learning immersion, and educational satisfaction. The collected data were analyzed using path analysis. Results The indirect effect of the path between instructional design and educational satisfaction, mediated through learning immersion in virtual environment simulation was found to be significant. Furthermore, the direct path was also statistically significant. Conclusion Educational content, based on virtual environment simulation, should be implemented based on instructional design. It is necessary to recognize the importance of instructional design that can promote learning immersion in virtual environment simulation, as well as to prepare consistent standards for such design.